The Hacker Conference: A Ritual Condensation and Celebration of a Lifeworld. - Coleman, Gabriella (Anthropological Quarterly)
This piece draws on ethnographic experience at various hacker conferences to rethink how face-to-face interactions work in concert with digital interactivity to constitute social worlds. Through a process of ritual condensation and emotional celebration, the conference works to perform and thus confirm what are otherwise more frequent, though more prosaic forms of virtual sociality. This focus allows me to decenter the historical priority placed on digital interactivity and examine the complementary and intertwined relationships between face-to-face interactions and online interactivity among a group of people often thought of as the quintessential digital subjects. More generally, approaching the conference in light of its ritual characteristics may also demonstrate how social enchantment and moral solidarity, often thought to play only a marginal role in the march of secular and liberal modernity, is in fact central to its unfolding.